Theranostic magnetic resonance imaging of type 1 diabetes and pancreatic islet transplantation - Wang, Ping; Moore, Anna (Quantitative Imaging in Medicine and Surgery; Vol 2, No 3 (September 27, 2012): Quantitative Imaging in Medicine and Surgery, 2012)
Type 1 diabetes mellitus results in impaired insulin production by pancreatic islets due to autoimmunity. Islet transplantation has recently emerged as a promising treatment for this disease. To visualize and monitor endogenous and transplanted islets, non-invasive strategies are currently being developed. These include strategies for in vivo magnetic resonance imaging of microvascular changes during diabetes development, tracking the recruitment of diabetogenic T cells to the pancreas, and imaging of endogenous and transplanted islet mass. The combination of MR imaging agents with therapy is a novel state-of-the-art theranostic approach that has a tremendous potential for type 1 diabetes management. Though still in its infancy, theranostic MR imaging has shown certain encouraging progress. Here we provide an overview of the latest accomplishments in this area as it applies to changes in islet vasculature during diabetes development, monitoring autoimmune attack mediated by T cells, and imaging of transplanted islets. Future challenges and opportunities in the area of theranostic MRI are discussed as well.